An investigation of selected mechanical and physical properties of young, unseasoned and finger-jointed Eucalyptus grandis timber - Crafford, Philippus Lodewicus (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScFor)--Stellenbosch University, 2013.